A Framework for Assessing the Performance of Cap-and-Trade Systems: Insights from the European Union Emissions Trading System. (20th June 2018) - Fuss, Sabine; Flachsland, Christian; Koch, Nicolas; Kornek, Ulrike; Knopf, Brigitte; Edenhofer, Ottmar
Abstract: The performance of the European Union (EU) Emissions Trading System (ETS) and other cap-and-trade schemes has been under scrutiny because of their inability to create a stable price for greenhouse gas emissions. This article seeks to inform the often confusing debate about the economic performance of cap-and-trade systems over time, with a focus on the EU ETS. Based on a simple intertemporal framework of emissions trading and a review of the literature, we show that different frameworks and notions of efficiency result in both different assessments of performance and different recommended strategies for improving performance. More specifically, we argue that if cap-and-trade systems have temporal flexibility (i.e., they include banking and borrowing of emissions allowances), it can be highly misleading to base the economic assessment on short-term efficiency. We seek to draw attention to the concept of long-term economic performance, which takes into account the intertemporal nature of emissions trading systems. In particular, we identify market and government distortions (e.g., myopia, lack of policy credibility, excessive discounting) that may depress allowance prices and hamper intertemporal efficiency. We then examine whether the recently adopted Market Stability Reserve and the alternative price collar are likely to address these distortions.